Sharia Banking Credit Crunch during Global Crisis - Wiratno, Eko; Hakim, Lukman; Daerobi, Akhmad (Journal of Economic Development, Environment and People, 2018)
This research was conducted examining factors which influences financial crunch as seen from the perspective of financing supply and demand sharia bank in Indonesia from January 2003 - June 2015. The secondary data were obtained from Statistics Indonesia (BPS), Bank Indonesia (BI) and Financial Services Authority (OJK). This research conducted with Two Stage Least Square (TSLS) approached. The results showed that financial crunch did not occured in sharia banking in Indonesia from January 2003-June 2015, Third Party Fund (DPK) negatively and significantly influences sharia banking financing supply, Non-Performing Financing (NPF) positively and non-significantly influences sharia banking financing supply, Profit Sharing Rate (TBH) positively and significantly influences sharia banking financing supply, Bank Indonesia Wadiah Certificate (SWBI) positively and non-significantly influences sharia banking financing supply, Bank Indonesia Certificate (SBI) positively and significantly influences sharia banking financing demand and Gross Domestic Product (PDB) positively and significantly influences sharia banking financing demand.